EDUKASI HALAL LIFESTYLE MELALUI PEMBELAJARAN BERBASIS PRODUCT KNOWLEDGE BAGI SISWA SMA MUHAMMADIYAH 2 SIDOARJO - Ima Faizah; Puspita Handayani; Anis Farihah (LPPM Universitas Bina Bangsa, 2023)
Halal is a guarantee of security, tranquility and health for humans. Halal has become a need and lifestyle for people across religions. The development of the industry in various fields demands to be more aware of the product's halal status. Teenagers as one of the targets for new products must have adequate knowledge in identifying the halalness of the products they will buy. This community service activities aim to increase student knowledge regarding the scope of halal and how to identify criteria for halal products. The method used is through halal lifestyle education by using a product knowledge-based learning approach based on aspects of the halal logo, composition, name, and product shape. The results of the activity show that halal lifestyle education with product introduction-based methods is of interest to students and can increase knowledge and skill in recognizing halal product, and also motivate students to implement a halal lifestyle